Pre-nuclear level of 129I in Chinese loess-paleosol sections: A search for the natural 129I level for dating in terrestrial environments. (15th June 2018) - Fan, Yukun; Zhou, Weijian; Hou, Xiaolin
Abstract: Due to its long half-life (15.7 Myr), radioactive 129 I has great potential for dating geologic materials as old as 100 Myr. Thus, knowing the natural level of 129 I is crucial to dating applications. The initial ratio of 129 I/ 127 I in the ocean has been quantified by a number of researchers who have reached a consensus value. However, the applicability of 129 I dating in the terrestrial environment remains problematic because the lack of an initial 129 I/ 127 I value. In this work, samples of loess-paleosol sections from the Chinese Loess Plateau (CLP) were analyzed for 129 I/ 127 I, aiming to provide an initial 129 I/ 127 I ratio that can be adopted for dating purposes in terrestrial environments. A value of (2.0 ± 1.0) × 10 −11 for the 129 I/ 127 I ratio was found in two investigated loess-paleosol sections from Xifeng and Luochuan, China. This ratio is one order of magnitude higher than the initial value reported for the marine environment. Alteration of the natural initial 129 I in the investigated samples due to the downward migration of anthropogenic 129 I and by excess fissiogenic 129 I from uranium was not supported. Consequently, the 129 I/ 127 I ratio measured is considered to be a pristine value, and the difference from that in the marine systems is attributed to an isotopic dilution effect.